IMPROVING NURSE RETENTION AT SINAR HUSNI HOSPITAL MEDAN THROUGH ORGANISATIONAL COMMITMENT AND MANAGEMENT OF JOB STRESS - Yuli Arnida Pohan; Rosmala Dewi; Nagian Toni (Bajang Institute, 2025)
Low nurse retention rate is one of the serious challenges in hospital management, especially in maintaining health service stability and operational sustainability. This study aims to examine how organisational commitment and job stress management can contribute to improving nurse retention. Using a quantitative approach, data was collected through distributing questionnaires to nurses working in a hospital environment. The results showed that high organisational commitment is able to build a sense of belonging and loyalty in nurses, while effective management of work stress creates a more comfortable and supportive work environment. These two factors proved to have a significant effect on nurses' desire to stay in the long term. The findings are expected to serve as a basis for hospital management in designing retention strategies that focus more on the well-being and emotional attachment of health workers